Alignment of teeth using different aesthetic orthodontic techniques (conventional buccal technique, lingual technique and Inman Aligner): In vitro study - Gasgoos, Saad Sami; Mahmood, Rawand Ahmed (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objective: An expectation of beautiful smiles at the end of orthodontic treatment is a primary concern to each patient, but is also equally concerned with appearance while undergoing treatment. The development of appliances that combine both acceptable aesthetics for the patient and adequate technical performance for the clinician is the ultimate goal. The aim of this study was to compare three different aesthetic orthodontic techniques with different biomechanics in order to quantify the efficiency of these techniques in alignment of displaced upper right central incisor and investigating the effects of these variables on alignment considering its tipping and rotation. Methods: The sample consisted of three groups with each group including 15 samples; (1) conventional buccal technique group, (2) lingual technique group and (3) Inman Aligner group, all on a typodont simulation system (dentsply). Preoperative and postoperative digital images were taken and analyzed using Autodesk AutoCAD software. Results: The conventional buccal technique gave rise to the highest mean of tooth tipping and rotation followed by the lingual technique. The Inman Aligner produced the least level of tooth tipping and rotation. Conclusion: The best method of alignment is the conventional buccal technique followed by the lingual technique. The least favourable one is the Inman Aligner.